FUNGSI EKOWISATA SEBAGAI SARANA EDUKASI PELESTARIAN HUTAN TROPIS DI KABIL, BATAM - Robert Halim; Diah Anggraini (Jurusan Arsitektur dan Perencanaan, 2021)
Forests are one of the largest oxygen producers on Earth and are home to many types of plants and animals. The existence of forests on Earth is very important because their absence would have fatal consequences for all life. One of the impacts due to the reduced number of forests is global warming, flooding, reduced oxygen supply and landslides. The word deforestation is no longer a